Effect of strontium deficiency on the structural, magnetic and magnetocaloric properties of La0.65Eu0.05Sr0.3−xMnO3 (0 ≤ x ≤ 0.15) perovskites. Issue 79 (28th August 2015) - Bellouz, Ridha; Oumezzine, Marwène; Dinia, Aziz; Schmerber, Guy; Hlil, El-Kebir; Oumezzine, Mohamed
<x xml:space="preserve">Abstract</x> We have investigated the effect of nominal strontium deficiency on the structure, magnetic and magnetocaloric properties of La0.65Eu0.05Sr0.3−xMnO3 (x = 0, 0.10 and 0.15) perovskites.